Hubungan Novel Demian The Story of Emil Sinclair’s Youth Karya Hermann Hesse dengan Lirik Lagu Grup Musik BTS dalam Album Wings, serta Pengaruhnya Terhadap ARMY Indonesia: The Connection of Demian’s Novel the Story of Emil Sinclair’s Youth by Hermann Hesse with the Song Lyrics of the BTS Music Group in the Wings Album, and Its Effect on the Indonesian ARMY - Miftahul Jannah; Mochammad Asyhar; Muhammad Syahrul Qodri (Jurnal Bastrindo, 2022)
Abstrak: Penelitian ini bertujuan untuk mengetahui bagaimana hubungan novel Demian The Story of Emil Sinclair’s Youth karya Hermann Hesse dengan lirik lagu yang terdapat dalam album Wings yang dibawakan oleh BTS, serta pengaruhnya terhadap ARMY Indonesia. Penelitian ini merupakan jenis penelitian kualitatif menggunakan teori interpretatif simbolik Clifford Geertz dengan pendekatan sosiologi sastra. Berdasarkan hasil analisis diketahui terdapat tiga simbol kebudayaan, yakni simbol agama, simbol pantang menyerah, dan simbol kritik. Adapun pengaruh terhadap ARMY Indonesia adalah (1) sikap toleransi antarumat beragama di kalangan ARMY semakin kuat, (2) sikap pantang menyerah yang diteladani ARMY diimplementasikan dalam kehidupan sehari-hari, dan (3) menumbuhkan sikap berani berpendapat terhadap fenomena sosial  yang ada  melalui berbagai cara, seperti saling berbagi pesan kebaikan melalui forum ARMY di sosial media, membantu me-repost berita terkait dengan isu sosial, dan menulis. Abstract: The study aims to find out the relation of Demian’s novel The Story of Emil Sinclair’s Youth by Hermann Hesse and the  lyrics from the Wings album, as well as its effect on the Indonesian ARMY. The gathered data is analysed using Clifford Geertz's symbolic interpretation theory with a sociology of literature approach and is presented using qualitative method. The result reveals that three cultural symbols are used in the album, namely religious symbols, signs of permissiveness, and symbols of criticism. Furthermore, three major impacts on the Indonesian ARMY are found, they are: (1) the growing religious tolerance among the ARMY community, (2) exemplifying of unyielding attitude and their implementation in daily life, and (3) increasing courage to speak up about social issues, including sharing messages of kindness in the ARMY forums, and rising awareness about social issues by reposting news and writing.